“This is what black girls do”: lamenting the bruised umntu and resisting dehumanisation - N. Penxa-Matholeni; D. Abrokwaah (Acta Theologica)
This article seeks to analyse the infamous urine incident that happened at Stellenbosch University in May 2022. This analysis will be done in relation to space, language, and belonging. The question is: To what extent does the urine incident relate to the issues of space, connection through language, and belonging at Stellenbosch University? Indigenous storytelling methodology is employed to answer the above question. The metaphors of amaXhosa (umntu ngumntu ngabantu1 and endleleni2) are used to find a connection and pave the way forward.